IMPLEMENTASI KELOMPOK KERJA GURU (KKG) DALAM PELAKSANAAN TUGAS GURU (Studi Deskriptif Kuantitatif di PAUD Gugus Anyelir Kecamatan Muara Bangkahulu Kota Bengkulu) - Lissa Puji Khasanah; Sumarsih Sumarsih; Yulidesni Yulidesni (Universitas Bengkulu, 2018)
This research is aimed to describe Implementation of Teacher Group (KKG) In The Implementation of Teacher Task. The method of this study is a quantitative descriptive. The population of this study is all of Early Childhood Education teachers who are teaching in Early Chilhood Education Anyelir Group Muara Bangkahulu Subdistrict Bengkulu City. For the sample, the writer used total sample which consists of 37 teachers.The technique for collecting the data is used questionnaire. And for the data analysis is used percentage technique. The results of the study showed implementation of Teacher Group (KKG) in the implementation of teacher task is on a verry good category with the score 81%. For the specification, the implementation of the KKG in the implementation of teacher tasks in the implementation stage of learning is very good with 86,5% score, for the implementation of the KKG in the implementation of teacher tasks in the implementation stage of learning is on the good category which has score 78%, and for the implementation of the KKG in the implementation of teacher duties at the learning evaluation stage on the verry good category with 94,6% score. The writer suggests for the next researcher to do the deeper research abouth the aspects of Implementation KKG in Early Chilhood Education by involving broader subject and more deeply so as to give meaningful contribution to the theoretical level about KKG.